DESIGN MODIFICATION OF INPUT PUSHER ASSEMBLY OF LASER MARKING MACHINE (Case study at Integrated Circuit Assembly Manufacturing) - Hakim, Arif Rahman (JURNAL DIMENSI, 2012)
Laser marking process is one of the process step in Integrated Circuit (IC) assembly manufacturing. This process is to mark the IC unit with the device information, assembly information and product brand. One type of lead frame used for IC assembly is open end lead frame which causing the individual lead on end unit prone to damage due to hard mechanical contact. At laser mark process, the lead frame will be pushed into the laser chamber by using a solid input pusher. The existing design of input pusher will push the lead by making contact with the edge of the lead frame. Production section keep observing the damage lead problem occurred when process the open end lead frame. Damage lead was 54% of the defect occurred at laser mark process. This problem causing low yield and high rework. Team has been established to analyze the problem and found the solution.Through investigation and analysis, team found the root cause of the problem and takes the appropriate corrective action. Design modification of input pusher from the previous design which was solid type to be U-type significantly reduces the damage lead at laser mark process.   Initial observation showed that the new design able to reduce 98% of damage lead. Key word : Design modification